Characteristics of Pregnancy and Birth Outcomes among Expectant Teenage Mothers: A Single Center of Retrospective Study of 10 Years Approach - Tanjaya, Hendri; Riani, Mutiara; Darmawan, Budi; Mardjuki, Edihan (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aims to analyze the characteristics and birth outcomes of Indonesian adolescents who have experienced pregnancy.Methods: This study assessed hospital-based retrospective cross-sectional study of 112 deliveries of teenage pregnancy. Bivariate analysis was conducted to examine the direct impact of each independent variable on the outcome variable. Following bivariate analysis, assumptions for logistic regression were examined using a variable with a p-value of <0.25.Result: Adolescent pregnancy was associated with a notably higher risk of anemia, postpartum hemorrhage, and low Apgar score at birth at 1 minute (p<0.05). Moreover, most adolescent pregnancies show complications. However, the rate of cesarean section deliveries was lower.Conclusion: Adolescent pregnancies are associated with negative effects on neonates and maternal figures. It remains a severe health problem that impacts all countries worldwide. Adolescence is not a good period for pregnancy. Improving the quality of health education and healthcare services is crucial for better outcome of adolescent pregnancy.Karakteristik Kehamilan dan Hasil Persalinan pada Kehamilan Remaja: Sebuah Studi Tunggal, Studi Retrospektif dengan Pendekatan 10 TahunAbstrakTujuan: Penelitian ini bertujuan menganalisis karakteristik dan prognosis persalinan pada remaja di Indonesia.Metode: Sebuah studi potong lintang retrospektif berbasis rumah sakit terhadap 112 persalinan dari kehamilan remaja dilakukan dalam penelitian ini. Analisis bivariat dilakukan untuk memeriks a dampak langsung dari setiap variabel independen terhadap variabel dependen. Regresi logistik dilakukan dengan menggunakan variabel yang memiliki nilai p kurang dari 0,25 setelah analisis bivariat.Hasil: Kehamilan remaja dikaitkan dengan risiko anemia yang lebih tinggi, perdarahan pascapersalinan, dan skor APGAR yang rendah saat lahir pada menit ke-1 (p<0,05). Sebagian besar kehamilan juga mengalami komplikasi. Namun, tingkat persalinan operasi caesar lebih rendah.Kesimpulan: Kehamilan pada remaja berkaitan dengan berbagai komplikasi pada ibu dan neonatus, sehingga menjadi masalah kesehatan yang memengaruhi negara di seluruh dunia. Masa remaja bukanlah periode ideal untuk kehamilan, sehingga diperlukan upaya untuk meningkatkan kualitas pendidikan kesehatan dan layanan kesehatan guna memperbaiki prognosis kehamilanKata Kunci: Kehamilan, Komplikasi, Prognosis kehamilan, Remaja